Role of a gitogenin-type steroidal saponin (3-O-β-d-glucopyranosyl (1 → 2)-β-d-glucopyranosyl (1 → 4)-β-d-galactopyranoside-25R, 5α-spirostane-2α, 3β-diol), isolated from the leaves of Malvastrum coromandelianum in regulating thyrotoxicosis in rats. Issue 19 (1st October 2016) - Panda, Sunanda; Kar, Anand
Graphical abstract: Abstract: The hitherto unknown role of saponin in the regulation of thyrotoxicosis has been revealed in chemically-induced thyrotoxic rats.l -T4 (l -thyroxine) administration at pre-standardized dose of 500-μg/kg body weight for 12 days increased the levels of thyroid hormones, enhanced the activity of hepatic 5′-monodeiodinase I (5′DI) and glucose-6-phosphatase (G-6Pase) as well as lipid peroxidation (LPO) with a parallel decrease in the levels of antioxidative enzymes. However, administration of the isolated saponin for 15 days ameliorated the T4 -induced alterations in serum thyroid hormones, hepatic LPO, G-6-Pase and 5′DI activity, and improved the cellular antioxidant status, indicating its antithyroidal and antioxidative potential. These effects of the test compound were comparable to a reference antithyroid drug, Propylthiouracil (PTU), suggesting that the test saponin may act as a potent anti-thyroid agent.